Association of Peripheral Artery Disease, Peripheral Neuropathy and Insulin Resistance among Patients with Type 2 Diabetes mellitus in Ekiti, Nigeria (African Journal of Biomedical Research, 2022)
Peripheral arterial disease (PAD), a reflection of systemic atherosclerosis, is a clinical condition that manifest as atherosclerosis of the lower limb. The study determined the association among PAD, peripheral neuropathy (PN), and insulin resistance (IR) in patients with type 2 diabetes mellitus (T2DM). A cross-sectional study was conducted among patients with T2DM attending the endocrine clinic of Ekiti State University Teaching Hospital (EKSUTH), Ado-Ekiti, between October to December 2018. Demographic information such as age, gender, and duration of diabetes were documented in a questionnaire, while anthropometry, systolic and diastolic blood pressures (SBP & DBP) were determined. PAD, PN, and IR were determined by ankle brachial index (ABI), vibration perception threshold (VPT) to biothesiometer and homeostasis model (HOMA2-IR) respectively. Association among variables of interest were determined with Pearson’s Chi-Square, Student’s t test, and Pearson’s correlation. There were 90 participants, with a mean age of 58.7(11.6) years. The prevalence of PAD was 40% (37.0% in men and 40.7% in women, p =0.36), and 12.2% had moderate PAD. Compared to patients without PAD, those with PAD had higher mean HOMA2-IR (3.71 vs 2.01, p